The existence on great Sheikh Muhyiddin Ibn al-Arabi | الجانب الوجودي عند الشيخ الأكبر محيي الدين ابن العربي - Muhammad Yunus Masruhin (Fakultas Dirasat Islamiyah, Univitas Islam Negeri (UIN) Syarif Hidayatullah Jakarta, 2010)
As a great thinker, the author of the book